The Impact of Da'wah Message Communication from TikTok Account @Kadamsidik00 on Students of the QurÔÇÖanic and Tafsir Studies Program at UIN Mahmud Yunus Batusangkar - Kholijah, Siti; Mastanora, Refika; Catherine, Sarkissian (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
Contemporary da'wah demands approaches that align with the development of technology and the culture of digital communication. TikTok, as a short-form video-based social media platform, has become a new space for preachers (da'i) to convey Islamic messages that are relevant to the lives of the younger generation. The TikTok account @kadamsidik00 actively utilizes this medium to deliver da'wah in the form of reflective, educational, and inspirational content. This article aims to analyze the communication effects of contemporary da'wah messages delivered by this account on the cognitive, affective, and conative changes of students in the QurÔÇÖanic and Tafsir Studies Program (IAT) at UIN Mahmud Yunus Batusangkar. The approach used is descriptive qualitative. The results show that contemporary da'wah messages through TikTok can enhance studentsÔÇÖ Islamic understanding (cognitive), shape positive religious attitudes and spirituality (affective), and encourage more active religious practices (conative).